ANALISIS KELAYAKAN BISNIS UMKM SALMAN ORANGE JUICE (SOJ) DI KOTA PALU - Tina Sintiani; Dewi Junita Purwanti; Munawarah; Muhammad Din (Jurnal Nusa Manajemen, 2026)
This study aims to analyze the feasibility of the Salman Orange Juice (SOJ) micro-enterprise in Palu City, which produces fresh orange drinks based on local raw materials. Data were obtained through interviews with the business owner, field observations, and financial documentation. The analysis used qualitative and quantitative descriptive approaches, with investment feasibility indicators including Net Present Value (NPV), Profitability Index (PI), Payback Period (PBP), and Internal Rate of Return (IRR), using a 10% discount rate. The results indicate a positive NPV of Rp4,600,000, a PI of 1.23, a PBP achieved in 0.74 years or approximately 9 months, and an IRR of 35.3%. All calculations indicate that the SOJ business is feasible to operate and develop further. From a non-financial perspective, this business also supports local economic empowerment by utilizing orange raw materials from local farmers, offering healthy beverage products, and has a potential market, especially among university students. Thus, the SOJ business not only provides financial benefits but also has a positive socio-economic contribution.